2016
DOI: 10.1016/j.jsps.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tramadol on metamizol pharmacokinetics and pharmacodynamics after single and repeated administrations in arthritic rats

Abstract: Combined administration of certain doses of opioid compounds with a non-steroidal anti-inflammatory drug can produce additive or supra-additive effects while reducing unwanted effects. We have recently reported that co-administration of metamizol with tramadol produces antinociceptive effect potentiation, after acute treatment. However, none information about the effect produced by the combination after chronic or repeated dose administration exists. The aims of this study were to investigate whether the antin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…In the same way, for the MET‐4D and MET+MOR‐4D schedules, the relationship was also characterized by a counter clockwise hysteresis loop for the MAA metabolite and a clockwise hysteresis loop for the AA metabolite plasma concentrations (Data not shown). For this reason, to define the PK/PD relationships, the AUC of the antinociceptive effect (global antinociceptive effect) instead of FI% to be related to metabolite concentrations was used …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the same way, for the MET‐4D and MET+MOR‐4D schedules, the relationship was also characterized by a counter clockwise hysteresis loop for the MAA metabolite and a clockwise hysteresis loop for the AA metabolite plasma concentrations (Data not shown). For this reason, to define the PK/PD relationships, the AUC of the antinociceptive effect (global antinociceptive effect) instead of FI% to be related to metabolite concentrations was used …”
Section: Resultsmentioning
confidence: 99%
“…In certain combinations of analgesic drugs, it has been shown that it is not only possible to reduce the risk of incidence of adverse effects associated with the administration of high doses of the individual drugs, but also to increase the antinociceptive effects . However, although some preclinical and clinical studies had shown that such combinations can produce analgesic potentiation, little it is known about the antinociceptive effects after repeated administrations . A useful therapeutic focus within the context of chronic pain treatment is to maximize therapeutic efficacy while minimizing deleterious side effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bolus doze tramadola i metamizola se niz godina koriste za kupiranje bola, akutnog i hroničnog. Međutim, na osnovu farmakoloških istraživanja koja su dokazala da ne postoji interakcija između ova dva leka ukoliko se oni primene istovremeno, u istom rastvoru 13 , kontinuirani i istovremeni način primene se u mnogim studijama pokazao kao bolji terapijski izbor [14][15][16][17][18][19][20][21][22] . Takođe, u istim studijama je vršeno poređenje efekta tramadol/metamizol kombinacije sa drugim analgetskim režimima za različite vrste operacija, u kojima se ispitivana kombinacija pokazala različito efikasnom u poređenju sa drugim analgetskim reži-mima.…”
Section: Diskusijaunclassified